Leiomyosarcoma of the nasal cavity - Saadoun, Rakan; Obermueller, Theresa; Franke, Mareike; Schell, Angela; Mückner, Kersten; Riemann, Randolf (ENT, 2022)
Leiomyosarcoma (LMS) in the sinonasal tract (SNT) is a rarity that has been firstly described in 1958. Since then, there have been only a few articles about this entity. Most of the data available about LMS in the SNT is derived from case reports. We believe that our case will support the data set and help guiding the management of this rare condition. A 84-year-old female presented with nasal airway obstruction on the left side. She experienced several episodes of epistaxis from her left nostril, what made her to seek medical care. A rhinoscopy revealed an obstructing mass in the left nasal cavity. Computed tomography (CT) scan of the paranasal sinuses revealed a homogenous mass occupying the left nasal cavity, bone destruction of the left middle, and inferior nasal turbinates. An infiltration of the left nasolacrimal duct was also present. The patient refused to undergo open surgery and the mass was removed during an endoscopic approach. The histopathological analysis combined with immunohistochemistry was consistent with LMS. The resection margins were positive for tumor cells. A staging with CT-neck-thorax, abdomen ultrasound, and MRI of the head ruled out metastases. She underwent a second endoscopic tumor resection surgery with positive resection margins and obtained adjuvant radiotherapy. On 9 months of follow-up, there was no recurrence or metastases.